Academic Advising and the Evaluation of Student Petitions: A Vehicle for Student Equity and Justice - Guerrero, Ernesto (Allies for Education, 2019)
At some universities, academic advisors manage the evaluation of petitions, while at others it is the responsibility of the Registrar’s office. For the purposes of this article, petitions are requests initiated by students for some sort of exception to a stated rule or policy. Decisions a university makes on these types of petitions can have long-reaching implications for a student’s time to degree, GPA, and even degree completion. As a result, those who evaluate these petitions and the processes they use to make these evaluations, play a central role in student success and retention. Based on the literature and my own professional experience, I argue that academic advisors are the individuals best qualified to evaluate these cases, and that this contributes to institutional equity as it reduces administrative barriers for students.